Purple Corn Silk Extract Attenuates UVB-Induced Inflammation in Human Keratinocyte Cells - Watcharaporn Poorahong; Sukanda Innajak; Malyn Ungsurungsie; Ramida Watanapokasin (MDPI AG, 2022)
UVB is a causative factor for severe skin damage, such as cell aging, death, and inflammation. UVB easily permeates into the epidermis layer of human skin, which is mainly composed of keratinocyte cells. In previous results, we found that purple corn silk (PCS) extract showed the potential to inhibit keratinocyte damages of UVB-treated cells. Thus, in this study, we aimed to evaluate the preventive effects of PCS extract against the inflammation of UVB-induced keratinocyte cells using the HaCaT cell line. HaCaT cells were treated with PCS extract at various concentrations for 1 h, then exposed to 25 mJ/cm2 UVB before subsequent experiments. Fragmented DNA was observed using flow cytometry. The inflammatory response was investigated through NF-κB activity by immunofluorescence staining and related protein expression by Western blotting. The results demonstrated that PCS extract decreased the sub-G1 DNA content. Interestingly, PCS extract attenuated NF-κB activity via suppressed NF-κB nuclear translocation and protein expression. Moreover, PCS extract remarkably decreased c-Jun phosphorylation and decreased proinflammatory cytokines, along with iNOS and COX-2 levels in UVB-treated cells compared to the UVB-control group. This finding exhibited that PCS extract minimized inflammation in keratinocyte cells induced by UVB radiation.